Controllable fabrication of elastic foam with ordered helical carbon nanofiber arrays - Siren Guo; Xialong Cai; Rongling Zhang; Wei Feng; Hanjun Wei; Ying Li (eXPRESS Polymer Letters)
In this work, a foam composed of helical carbon nanofiber arrays was successfully synthesized via chemical vapor deposition. By controlling synthesis parameters including the synthesising temperature and gas flow rate, carbon nanofibers with straight, kinked, and spring-like morphologies were obtained. Adjusting the precursor feed led to the formation of foams with well-ordered carbon nanofiber structures. The nanofibers exhibit diameters ranging from 98 to 175 nm and lengths extending to the centimetre scale. Experimental results confirm that these fibers are organic carbon nanofibers, attributed to low-temperature catalytic synthesis. Structural characterization reveals that the catalyst assumes a regular polyhedral shape and becomes embedded within the fibers, which symmetrically grow from both faces of the catalyst. Structural analysis indicate that the carbon nanofibers are hollow, multi-walled structures with numerous defects. The resulting foam demonstrates porous, along with excellent elasticity and high mechanical strength.